PENGARUH PELVIC ROCKING EXERCISE TERHADAP PENGURANGAN NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III DI PMB “E” WILAYAH KERJA PUSKESMAS BULULAWANG KABUPATEN MALANG: Effect Of Pelvic Rocking Exercise On Pain Reduction Background On Trimester III Pregnant Women In Pmb “E” Working Area Of Bululawang Puskesmas, Malang District - Anggrawati Wulandari (LPPM - STIKES Pemkab Jombang, 2021)
ABSTRACT Women who have had back pain before pregnancy are at higher risk of experiencing the same thing when pregnant. Therefore, it is very important to be able to differentiate pregnancy back pain from back pain that occurs due to other causes. The purpose of this study was to analyze the effect of Pelvic Rocking exercise on the reduction of back pain in trimester III pregnant women in the Bululawang Community Health Center, Malang Regency. This research design uses correlational analytic with one group pre test design approach. The population in this study were all pregnant women in PMB